Geoinformation Technology and Artificial intelligence - Davies, Kaylin (New York Syrawood Publishing House, 2023)
Geoinformation technology refers to a science that deals with the acquisition, storage, management, analysis and delivery of geographic and spatially referenced information. It comprises an interactive site for deeper study of raster data on greenhouse gas emissions as well as a website for spatial analysis and visualization of vector data. Artificial intelligence (AI) is a field of computer science that focuses on developing and managing technology that can learn to make decisions and perform actions autonomously on behalf of humans. It uses logic-based techniques and advanced analysis including machine learning to assist and automate decisions, interpret events, and take actions. The combination of geoinformation technologies and AI technologies has various applications such as exposure modeling in environmental epidemiology and automating cyber-physical systems. This book elucidates the concepts and innovative models around prospective developments with respect to the application of artificial intelligence in the field of geoinformation technology. It will serve as a valuable source of reference for graduate and postgraduate students.
Keywords: Geophysics; Geographic information system; Artificial Intelligence